Analysis of Delay Factors in Drinking Water Supply System Development Projects on Small Islands (Case study of the Drinking Water Supply System Project on Maratua Island) - Febiana, Indra; Rachmat, Agus; Kadir, Yushar (Journal of Current Research In Multidisciplinary, 2025)
To fulfill cost, quality, and schedule restrictions, construction projects must carefully plan, execute, and oversee project management. Construction delays frequently raise expenses and lower quality. An operational Water Supply System (SPAM) is essential in distant places like tiny islands. The Seawater Reverse Osmosis (RO) SPAM Project on Maratua Island deviated 6% from the contract timeline. This study analyzes and ranks delay factors in SPAM project development on Small Islands. This study collected primary data from 90 respondents (30 Consultants, 30 Executors/Contractors, and 30 Owners/Ministry of PUPERA) using non-experimental surveys. Validity and reliability testing, the Index of Importance for ranking, and Factor Analysis (PCA) to minimize and cluster the 23 original variables were performed. PCA divided the variables into three main categories that explained 61.808% of variation. Transportation, Geographical Location, Material, and Equipment were the biggest factor, accounting for 51.801% of variation. This component includes logistical challenges like distant site transportation and import delays. Second was Manpower, Scope Changes & Work Documents (5.404%), then Planning and Coordination (4.603%). Poor contractor job performance was the biggest delay issue. To reduce delays in small island SPAM projects, logistics planning and integrated multi-party project management must be urgently evaluated.